2022
DOI: 10.1021/jacs.2c06332
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Activation of S8 by Cucurbiturils in Water and Mechanism of Reduction to H2S by Thiols: Insights into Biological Sulfane Sulfur Trafficking

Abstract: Reactive sulfur species (RSS) play critical roles in diverse chemical environments. Molecules containing sulfane sulfur (S0) have emerged as key species involved in cellular redox buffering as well as RSS generation, translocation, and action. Using cucurbit[7]­uril (CB[7]) as a model hydrophobic host, we demonstrate here that S8 can be encapsulated to form a 1:1 host guest complex, which was confirmed by solution state experiments, mass spectrometry, and X-ray crystallography. The solid state structure of CB[… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…[56] Thanks to their unique structures, cucurbit-[n]uril (CB[n], n = 4-10) macrocycles have been used as supramolecular hosts and ligand molecules to prepare nanomaterials [57][58][59][60][61] and as catalysts and promoters. [62,63,72,73,[64][65][66][67][68][69][70][71] Cucurbit[n]urils can accommodate molecules inside their hydrophobic cavities to form host-guest inclusion complexes. The entrances to the cavity form both sides are lined with carbonyl groups that constitute a polar, negative portal.…”
Section: Resultsmentioning
confidence: 99%
“…[56] Thanks to their unique structures, cucurbit-[n]uril (CB[n], n = 4-10) macrocycles have been used as supramolecular hosts and ligand molecules to prepare nanomaterials [57][58][59][60][61] and as catalysts and promoters. [62,63,72,73,[64][65][66][67][68][69][70][71] Cucurbit[n]urils can accommodate molecules inside their hydrophobic cavities to form host-guest inclusion complexes. The entrances to the cavity form both sides are lined with carbonyl groups that constitute a polar, negative portal.…”
Section: Resultsmentioning
confidence: 99%
“…This observed pK a dependence matches what was observed in prior work with CB [7]/S 8 systems, in which the primary H 2 S generating pathway relies on the reduction of soluble S 0 carriers in free solution by thiols. 15 In the anionic surfactant system, the observed thiol pK a dependence means that the concentration of thiolate in solution directly impacts the rate of S 8 reduction, whereas this same dependence was not observed for cationic surfactants. The lack of pK a dependence for the cationic system suggests that either the positive micelle charge may attract the negatively charged thiols or alternatively shift the effective pK a of thiols within the local microenvironment.…”
mentioning
confidence: 95%
“…Using this system, we established that the encapsulated S 8 is initially attacked by a thiol to generate a soluble S 0 carrier that is further reduced to polysulfides and ultimately H 2 S by excess thiol. 15 Outside of host–guest chemistry, Steudel and co-workers also demonstrated that surfactants can increase the solubility of S 8 in water up to 0.103 mM in a chain length dependent manner, but the chemical accessibility of the solubilized S 8 was not investigated. 16 To further advance our understanding of modes of S 8 solubilization and activation, we demonstrate here that surfactants can not only solubilize S 8 in water but also promote the thiol-mediated reduction to H 2 S. Moreover, we show that anionic and cationic surfactants differentially impact the speciation and equilibria of S 0 carriers, highlighting how different hydrophobic microenvironments interface with different RSS (Fig.…”
mentioning
confidence: 99%
“…Supramolecular chemistry provides a wide range of receptor molecules, particularly macrocycles, that can be used as hosts in a variety of applications, garnering considerable interest from the scientific community. In terms of structural diversity, macrocycles, include cyclodextrins, , cucurbiturils, , crown ethers, cryptands, pillararenes, and calixarenes, , to give some examples. On the other hand, guest molecules are generally small molecules or ions that benefit from the host–guest interactions to improve their stability and bioavailability or even to tune their spectroscopic features, namely, colorimetric and fluorescent properties.…”
Section: Introductionmentioning
confidence: 99%